Ajanta : history and development. - Spink, Walter (Handbook of oriental studies. South Asia., 2014)
Volume 6 of Walter Spink's monumental and continuing study of the Ajanta caves, with over 350 illustrations, explains the gradual evolution of the site's architectural and sculptural features during Ajanta's remarkably brief development (462-480 CE).